BOARD CHARACTERISTICS AND REAL EARNINGS MANAGEMENT AMONG LISTED NON-FINANCIAL FIRMS IN NIGERIA - Abdulraheem Olayiwola KADIRI (Malete Journal of Accounting and Finance)
High expectations for earnings are put on companies, yet earnings management distorts how well those companies perform. Hence, this study examined the impact of board characteristics on real earnings management among listed non-financial companies in Nigeria. The study used a sample of 72 listed non-financial companies in Nigeria, covering the period of 2008-2020 on an unbalanced basis. The study was conducted over four (4) samples, vis-à-vis, the pre- and post-review of code of corporate governance and pre- and post-adoption of IFRS. The study employed the generalized method of moment (GMM) to estimate its empirical models. The findings from the estimation exercise revealed that board size reduces abnormal cash flows and abnormal production costs real earnings management after the review of code of corporate governance and adoption of IFRS but CEO duality promote real earnings management. Board independence was also found to reduce real earnings management while the number of meetings held by the board is ineffective in reduce earnings management. The study concluded that board characteristics are vital corporate governance mechanisms for reducing earnings management in Nigeria. It therefore recommended that an optimal size of board members as well as their independence should be emphasized for effective reduction in earnings management.